Quantum Meta-physics: Nonlocality and Limits of Determinism - Bartosz Wesół (Eidos. A Journal for Philosophy of Culture, 2023)
This essay aims to show that the recent development of quantum theory may provide us with an answer to one of the most compelling metaphysical problems, namely the problem of determinism. First, I sketch the conceptual background and draw the distinction between metaphysical and epistemological determinisms. Then, on the ground of the analysis of the problem of determinism in quantum mechanics, I argue that (1) metaphysical determinism is independent of quantum-mechanical formalism, and (2) that quantum nonlocality makes epistemological determinism impossible. I also try to show that metaphysical determinism should be regarded as a Kantian regulative idea which sets the horizon for scientific inquiry but which at the same time lacks what Kant calls “objective validity.” The main conclusion is that metaphysical determinism should be regarded as an idealization – a formal, cognitive principle that we a priori assume and not something that we discover through scientific inquiry.